1974
DOI: 10.1111/j.1751-1097.1974.tb06597.x
|View full text |Cite
|
Sign up to set email alerts
|

LASER PHOTOLYSIS OF RETINAL AND ITS PROTONATED AND UNPROTONATED n‐BUTYLAMINE SCHIFF BASE

Abstract: The pulsed ruby laser (347 nm) flash photolysis technique has been used to measure the triplet-triplet absorption spectra and triplet lifetimes of trans -retinal, N-trans -retinylidene-nbutylamine (NRBA), and protonated NRBA (NRBAH') at room temperature. In methylcyclohexane solution, the triplet lifetimes are in the range 10-2Ops and decrease in the order NRBAH' > NRBA > trans-retinal. Intersystem-crossing efficiencies ($,sc) were determined by a comparison technique using anthracene and 1,Zbenzanthracene as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 49 publications
4
50
0
Order By: Relevance
“…21 We expected, then, that when we looked a t the triplet-triplet absorption ( A, , , 460 nm) and the isomerization signal (at X 380 nm) of R E T in MeOH, the signals would be similar in character to, but with magnitude reduced to about 16% of, those seen for R E T in M C H . While +T for R E T in M C H is 0.5, it is reduced to 0.08 in MeOH.…”
Section: Log [Io(t)/ix(t)l = Lellc1lomentioning
confidence: 95%
See 1 more Smart Citation
“…21 We expected, then, that when we looked a t the triplet-triplet absorption ( A, , , 460 nm) and the isomerization signal (at X 380 nm) of R E T in MeOH, the signals would be similar in character to, but with magnitude reduced to about 16% of, those seen for R E T in M C H . While +T for R E T in M C H is 0.5, it is reduced to 0.08 in MeOH.…”
Section: Log [Io(t)/ix(t)l = Lellc1lomentioning
confidence: 95%
“…21 The picture presented above gives a rather fragmentary view of the isomerization process of the chromophore in visual pigments. They found that $isom = 0.45 f 0.1 when the 1 1-cis-retinal is excited by triplet sensitizers but &om was only 0.004 f 0.001 when the retinal was irradiated directly.…”
mentioning
confidence: 99%
“…Moreover when rhodopsin is treated with the unique triplet sensitizer trimethyl-1,2-dioxetane, the protein is denatured and the Chromophore isomerized (42). Since the intersystem crossing yield in PRSB has been shown (14,43) to be beyond the experimental detection limit (< 0.001), a triplet-state model would require that in the pigment the rate of triplet formation increases by at least three orders of magnitude. An additional difficulty arises from the fact that radiationlass transitions from the lowest triplet (T 1 ) to the ground state singlet (S 0 ) are relatively slow processes.…”
Section: Studies Of Model Oompoundsmentioning
confidence: 99%
“…with C ij ¼ X a e i ðk a Þ À e 0 ðk a Þ ½ S aj (6) where C ij is generally called "the C matrix." Equation (5) shows that weighted time profile V i t i (i = 1,…, p) can be represented by a linear combination of populationñ n i ½ " ðñ n i ðt 1 Þ;ñ n i ðt 2 Þ; :::Þ T and the C matrix; this provides us with a method to determine the decay time constants, k i .…”
Section: 42mentioning
confidence: 99%
“…[5]. Since retinal has a high quantum yield of intersystem crossing (0.50-0.61) [6], the T 1 absorption spectra can be recorded by 355 nm excitation to the 1B u + singlet state. In the all-trans isomer, a monotonical rise of the T n ‹ T 1 absorption is seen within 100 ps.…”
mentioning
confidence: 99%